Implementation of Telemedicine for Millennial Parents with Speech Delay Children in Kindergarten - Evicha Lufhiana Sriyono; Akaat Hasjiandito (Universitas Pendidikan Ganesha, 2025)
Speech delay in early childhood requires proper intervention and guidance through access to health services and active parental involvement in language development stimulation. However, limited access to healthcare services, distance, time constraints, and the busy schedules of working millennial parents often become barriers to obtaining direct consultation and assistance. Therefore, the use of health technology such as telemedicine has emerged as an alternative solution to support the management of children with speech delay. This study aims to analyze the implementation of telemedicine, explore the challenges in its application, and identify the advantages and limitations of its use for millennial parents who have children with speech delay. This research employed a qualitative approach using a case study method. The research subjects consisted of three millennial parents who have children aged 4–5 years experiencing speech delay. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that the implementation of telemedicine facilitates parents in accessing consultation services related to speech delay management, particularly in terms of time, distance, and cost efficiency. These findings indicate that telemedicine has the potential to become an innovative strategy to support early intervention services and strengthen parental involvement in supporting children’s language development.